Concordance of Porphyromonas gingivalis colonization in families. - Tuite-McDonnell, M (1997)
Periodontitis is a widespread disease that appears to be due to a specific bacterial infection. Several species of bacteria have been investigated as potential pathogens, and particularly strong evidence links the presence of Porphyromonas gingivalis with indicators of periodontitis. Information concerning the transmission of P. gingivalis between human contacts may be important in determining risk factors for disease and developing preventive strategies. A few small studies have provided some evidence of transmission between related individuals, but no large-scale study of families that would reflect the typical transmission of this pathogen in the population has been reported. The purpose of this study was to investigate the transmission of P. gingivalis within randomly selected, extended families. The colonization status of 564 members of multigeneration families was determined, and the degree of concordance observed among members of these families was then compared to that expected to occur based on the prevalence of colonization in the population studied. A PCR assay was used for detection of P. gingivalis. Concordance in colonization was more frequently observed within entire families (P = 0.0000) and for spouses (P < 0.001), children and their mothers (P < 0.001), children and their fathers (P < 0.01), adults and their mothers (P < 0.005), and siblings (P < 0.05) than would be expected if P. gingivalis were randomly distributed in the population studied. Results showed that contact with an infected family member substantially increased the relative risk of colonization in these intrafamilial pairs. This indicates that P. gingivalis is commonly transmitted by contact with an infected family member.